DOI: 10.1007/978-0-387-77570-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Resistance in Leishmania and Possible Drug Targets

Abstract: Pregarded as the second-most dreaded parasitic disease after malaria (WHO). Visceral leishmaniasis or kala-azar, caused by Leishmania donovani, is the most fatal form of leishmaniasis afflicting millions of people worldwide. No vaccination is available against leishmaniasis and fast spreading drug resistance in these parasitic organisms is posing a major medical threat. All these emphasize the need for new drugs and molecular targets along with reappraisal of existing therapeutics. Identification and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Drug resistance phenotype can result due to decrease in drug uptake, efflux of drug from the parasites, loss of drug activities and alteration of drug targets. 2 The cell envelope is enclosed with a number of unique lipids that play an important role in parasite virulence. Most cellular lipids are embedded within membranes; membrane composition adds another level of complexity in the studied biological network.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance phenotype can result due to decrease in drug uptake, efflux of drug from the parasites, loss of drug activities and alteration of drug targets. 2 The cell envelope is enclosed with a number of unique lipids that play an important role in parasite virulence. Most cellular lipids are embedded within membranes; membrane composition adds another level of complexity in the studied biological network.…”
Section: Introductionmentioning
confidence: 99%
“…23 Additionally, it has been demonstrated that chronic parasite exposure to metals like arsenic, often found in low, but biologically meaningful, levels in aquatic and terrestrial matrices (10−100 ppb), can induce cross-resistance to antimony, as they belong to the same chemical group. 24 The close relationship between the environment and the spread of drug resistance highlights the need for implementing a One Health approach. 25 Such an approach acknowledges the interdependence between healthy people, healthy animals, and healthy environments, 26 and is increasingly recognized as a critical strategy toward more sustainable drug development.…”
mentioning
confidence: 99%
“…Another resistance mechanism involves the up-regulation of cytosolic oxidoreductases from the trypanothione synthesis pathways (e.g., tryparedoxin peroxidase and peroxyredoxin), inducing metal ion chelation through free reduced thiols . Additionally, it has been demonstrated that chronic parasite exposure to metals like arsenic, often found in low, but biologically meaningful, levels in aquatic and terrestrial matrices (10–100 ppb), can induce cross-resistance to antimony, as they belong to the same chemical group . The close relationship between the environment and the spread of drug resistance highlights the need for implementing a One Health approach .…”
mentioning
confidence: 99%